Retinal Manifestations of Incontinentia Pigmenti: A Case Series of 14 Patients Highlighting the Importance of Intravenous Fluorescein Angiography and the Benefits of Early Laser Photocoagulation. (January 2021) - Bryan, Jaimie; Issa, Reda; Bakall, Benjamin; Welch, Matthew; Bryan, J. Shepard
Purpose: This case series describes the nature and frequency of retinal manifestations in patients with incontinentia pigmenti (IP). Methods: This is a retrospective single-center case series of all known patients with IP who presented to Associated Retina Consultants (Phoenix, AZ) between May 2016 and April 2019. Twenty-eight eyes of 14 patients with a dermatologic diagnosis of IP were included (n = 28). Most patients underwent examination under anesthesia with fundus photographs and intravenous fluorescein angiography (IVFA). Results: Of the 28 eyes, 8 (28.6%) had abnormal retinal findings on fundus examination. Of the 26 eyes that had IVFA, 10 (38.5%) had abnormal findings: Seven eyes (26.9%) had peripheral ischemia, 2 (7.7%) had previous peripheral laser scarring, and 2 (7.7%) had active peripheral neovascularization. Three eyes with normal examination results were found to have mild ischemia by IVFA. Patients with ischemia confirmed by IVFA were treated with laser photocoagulation. During follow-up, 4 previously treated eyes received additional laser photocoagulation. No patients showed vision loss, vitreous hemorrhage, retinal detachment, or adverse effects of treatment. No patients required vitreoretinal surgery. Conclusions: IP is a potentially blinding disease. Our case series demonstrates the efficacy of early treatment and the importance of ancillary testing with IVFA and fundus photography.